Sexual assault, sense of belonging, depression and suicidality among LGBQ college students. (30th September 2020) - Backhaus, I; Lipson, S K.; Fisher, L B.; Kawachi, I; Pedrelli, P
Abstract: Background: There has been growing concern about the poor mental health of college student of gay, lesbian, bisexual, or questioning/queer (LGBQ) sexual orientation. Factors believed to negatively influence LGBQ student's health include discrimination and victimization such as sexual assault, whereas factors believed to positively influence mental health include cohesiveness and a sense of belonging. Little is known about how these might interact with each other. Therefore, the objective of this study was to compare the effect of sexual orientation, history of sexual assault and sense of belonging on depression and suicidality among LGBQ and heterosexual students. Methods: This is a secondary data analysis using a subset of available data from the 2017-2018 Healthy Minds Study dataset. The dataset was encompassed of self-report data from about 60, 200 college students across 60 campuses in the United States. Descriptive statistics and three-way interaction analysis using PROCESS macro models in SPSS were performed. Results: Students identifying as LGBQ reported more frequently to have experienced sexual assault, to suffer from depressive symptoms and to have suicidal thoughts than heterosexual students. Significant three-way interaction effects were found for sexual orientation, sexual assault and sense of belonging predicting depressive symptoms (b= -.06, p= .042, CI: -.12; -.00), and suicidality (b= -.10, p= .004, CI: -.01; -.003). The effect of sexual assault on mental health differed depending on sexual orientation and sense of belonging. Particularly among LGBQ students, high sense of belonging was protective in the presence of sexual assault, and its absence had a deleterious effect on mental health. Conclusions: There is a need to reduce mental health problems and sexual assault on college campuses and to foster a sense of belonging. Enhancing sense of belonging may represent a strategy to mitigate depression and suicidality, particularly among LGBQ students. Key messages: Mental health problems such as depression and suicidal ideation among sexual minority students remain highly prevalent in the United States. Increasing sense of belonging may moderate symptoms such as depressiveness and suicidal ideation.